Cultural adaptation and validation of an instrument about nursing critical thinking skills - Jacqueline Faria de Oliveira; Esperanza Zuriguel Perez; Maria Beatriz Guimarães Ferreira; Patricia da Silva Pires; Elizabeth Barichello; Maria Helena Barbosa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to validate the Nursing Critical Thinking in Clinical Practice Questionnaire regarding cultural aspects and metric properties. Methods: a methodological research carried out through cross-cultural adaptation, face and content validity, dimensional construct and known groups validity, test-retest reliability and internal consistency. 511 nurses from four hospitals participated in the study, of which 54 participated in retest. Results: the instrument validation for Brazilian Portuguese maintained equivalences, according to the original version. The dimensional validity demonstrated adjustment to the tetrafactorial structure of the original version (GFI=0.69). There were statistically significant differences in critical thinking skills between nurses with graduate degrees and who undertook training, reading articles, developing research and working in an institution with a longer time implementation of the Nursing Process. The instrument showed temporal stability (ICC 073-0.84; p<0.001) and adequate internal consistency (α=0.97). Conclusions: the instrument proved to be valid and reliable for the studied population.